Composition-based view of the firm as a promising approach to studying small businesses - Tehseen, Shehnaz *; Mughal, S. A.; Durst, S.; Shujahat, M.; Qureshi, Zuhaib Hassan; Kokkalis, P. (SciELO, 2019)
Paper aims: Extant Literature based on the resource-based view (RBV) of the firm suggests that it can be used to study organizations of all types and sizes. In essence, the RBV argues that firms that possess rare, non-imitable, valuable, unique, and non-substitutable resources will outperform firms that do not possess such resources. This study questions the applicability of this assumption to smaller businesses, which are likely to have common resources readily available in the market rather than rare, non-imitable, non-substitutable, unique, or valuable resources. The purpose of this study is to discuss whether the composition-based view (CBV) of the firm offers a more promising approach than the RBV to studying small businesses. Originality: This study is one of the first to tentatively suggest a change in theoretical approach when studying small businesses. Research method: A structured critical review approach is taken. Main findings: The findings reveal that the CBV offers a more promising and appropriate theoretical framework than the RBV for research on small businesses, whereas the RBV is better suited to research on larger firms. Implications for theory and practice: Future studies can use the RBV and the CBV to study large and small businesses, respectively